Steroid Hormones and Their Action in Women's Brains: The Importance of Hormonal Balance - Del Río, Juan Pablo; Alliende, María I.; Molina, Natalia; Serrano, Felipe G.; Molina, Santiago; Vigil, Pilar (Frontiers in Public Health, 2018)
Sex hormones significantly impact women's lives. Throughout the different stages of life, from menarche to menopause and all stages in between, women experience dramatic fluctuations in the levels of progesterone and estradiol, among other hormones. These fluctuations affect the body as a whole, including the central nervous system (CNS). In the CNS, sex hormones act via steroid receptors. They also have an effect on different neurotransmitters such as GABA, serotonin, dopamine, and glutamate. Additionally, studies show that sex hormones and their metabolites influence brain areas that regulate mood, behavior, and cognitive abilities. This review emphasizes the benefits a proper hormonal balance during the different stages of life has in the CNS. To achieve this goal, it is essential that hormone levels are evaluated considering a woman's age and ovulatory status, so that a correct diagnosis and treatment can be made. Knowledge of steroid hormone activity in the brain will give women and health providers an important tool for improving their health and well-being.